PERANCANGAN DESAIN INTERIOR CIP LOUNGE PADA BANDARA SEPINGGAN, BALIKPAPAN - Aditya, Ulfi; Permatasari, Rr Chandrarezky (Anggada : Jurnal Desain dan Seni, 2021)
The purpose of this study is to provide an overview of CIP Lounge, which is one of the facilities available at the airport, the facility is there to meet the needs of passengers in the passenger terminal area. purchased using the freedom of flight at the airport, existing space facilities in accordance with the user’s lifestyle, and supported space that can provide comfort and user satisfaction. CIP facilities (commercially important people) Waiting rooms are available for passengers who have the privilege of waiting time compilation, with complete facilities that provide special services that provide comfort and exclusivity that cannot be done in ordinary public waiting rooms. There search method used in this study uses the design research method using the flow CHAPTER I Introduction, CHAPTER II Data review, CHAPTER III Project Data Analysis, CHAPTER IV Planning Concepts, CHAPTER V Conclusions, and Suggestions. This CIP Lounge is located at Sepinggan Airport, Balikpapan, this Lounge serves both local and foreign passengers, therefore CIP Lounge which provides comfort at the airport is one of the secondary needs needed by passengers who want the privilege to support CIP Lounge activities Airport, and the results of this study are the concept of "Combination between Eastern Kalimantan Culture and Modern Contemporary" can be applied to the CIP Lounge Interior planning and in accordance with the concepts that have been determined.